2019
DOI: 10.1111/pedi.12907
|View full text |Cite
|
Sign up to set email alerts
|

Five heterogeneous HbA1c trajectories from childhood to adulthood in youth with type 1 diabetes from three different continents: A group‐based modeling approach

Abstract: Objectives Only a fraction of youth meet established targets for glycemic control; many experience deteriorating control over time. We compared trajectories of hemoglobin A1c (HbA1c) among youth from three trans‐continental type 1 diabetes (T1D) registries and identified clinical variables associated with the odds of following increasing vs stable trajectories. Research design and methods Analyses included longitudinal data from 15 897 individuals age 8 to 18 with T1D for at least 2 years and HbA1c measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 44 publications
(69 reference statements)
10
50
1
Order By: Relevance
“…Our results demonstrate that the impact of diabetes technology use on glycemic control was large, even after adjustment for SES, rivaling treatment effects of new diabetes medications ( 35 ). Although prior research has highlighted racial-ethnic disparities in diabetes technology among youth with type 1 diabetes ( 36 , 37 ), our results show that racial-ethnic disparities exist despite being covered for these devices. In addition, we show that Black YA had lower diabetes technology use than Hispanic YA, despite similar public insurance coverage rates and SES levels.…”
Section: Discussioncontrasting
confidence: 85%
“…Our results demonstrate that the impact of diabetes technology use on glycemic control was large, even after adjustment for SES, rivaling treatment effects of new diabetes medications ( 35 ). Although prior research has highlighted racial-ethnic disparities in diabetes technology among youth with type 1 diabetes ( 36 , 37 ), our results show that racial-ethnic disparities exist despite being covered for these devices. In addition, we show that Black YA had lower diabetes technology use than Hispanic YA, despite similar public insurance coverage rates and SES levels.…”
Section: Discussioncontrasting
confidence: 85%
“…In a study identifying specific trajectories of HbA 1c over age by using group‐based trajectory modelling in 7002 children with type 1 diabetes, a lower risk of high BMI was found in the low stable HbA 1c group compared to the identified intermediate stable, intermediate increasing and high stable HbA 1c groups 22 . With similar modelling in a multicentre study from Germany, Austria and the USA in more than 15 000 children aged 8–18 years, increasing HbA 1c trajectories were associated with higher BMIz compared to a low stable trajectory 23 . In line with the present study, this indicates that there is a group reaching target HbA 1c without increasing BMI.…”
Section: Discussionmentioning
confidence: 82%
“…Sustained hyperglycaemia is associated with diabetes complications and strict glycaemic control reduces both microvascular and macrovascular complications of diabetes (61,62). It has been shown that an increasing HbA1c trajectory is associated with higher BMI, lower linear growth, use of insulin injection therapy and severe hypoglycaemic episodes (63), and poor glycaemic control early in life is associated with microvascular disease (64). Perhaps the HbA1c trajectory, not just the value, may also define risk of vascular complications and thus impact our approach.…”
Section: Risk Factors For Diabetes Complicationsmentioning
confidence: 99%
“…Continuous subcutaneous insulin infusions using an insulin pump may reduce the risk of complications such as retinopathy and peripheral neuropathy (70). While it has been shown that the use of insulin pump therapy in some cohorts has been associated with improved glycaemic control (63,71), diabetes technology has not necessarily been associated with a sustained improvement in glycaemic control or reduction in complications (72). Few studies have examined glucose variability using continuous glucose monitoring and diabetes complications as the widespread availability of continuous glucose monitoring is relatively recent.…”
Section: Risk Factors For Diabetes Complicationsmentioning
confidence: 99%